Tidiane Diarra - Bouwèrè, Mali - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Tidiane Diarra, a young farmer from Mali, describes how the rainfall patterns have changed over the last years and how the village have had the opportunity to receive a weather station, which is helping the farmers of the area to adapt to changes. They can thus better monitor and predict the rainfalls. Tidiane also talks about the importance of capacity building and training for a farmer these days. Farmers need to receive proper support so that they can adapt to the climate changes, he explains, and be introduced to different seed varieties, selected according to the forecasted rainfall.